Effect of docosahexaenoic acid and olive oil supplementation on pup weight in alcohol-exposed pregnant rats - Yadav, Deepak; Ostrea, Enrique M.; Cheng, Charlie T.; Kisseih, Esther; Maddipati, Krishna R.; Thomas, Ronald L. (Frontiers in Pediatrics, 2024)
Low birth weight has been observed in offspring of alcoholic mothers due likely to unresolved inflammation and oxidative injury. Dietary lipids play a role in inflammation and its resolution. The primary objective was to investigate the effect of DHA and olive oil on the birth weight of pups born to alcohol-exposed dams. Pregnant rats were randomized to the control or three treatment (alcohol) groups. From gestational days (GD) 8-19, the control group received daily olive oil and malto/dextrose, whereas groups 2 and 3 received olive oil and low-dose alcohol or high-dose alcohol, respectively. Group 4 received daily DHA and high-dose alcohol. The dam’s blood was collected on GD 15 and 20 for cytokine analysis. Dams were sacrificed on GD 20. The mean birth weight of pups and mean placental weight of fetuses were compared by one-way ANOVA with post hoc Duncan’s test. There was a significant increase in the pups' mean birth weight in the high-dose alcohol/DHA and high-dose alcohol/olive oil. There was a significant increase in the placental weight in all three treatment (alcohol) groups. Higher pro-inflammatory cytokines (IL-1β and IL-12p70) were noted in the alcohol-exposed dams. DHA and olive oil supplementation in alcohol-exposed pregnant rats significantly increased their pups' birth weight despite having high pro-inflammatory cytokines. The mechanism of this effect remains to be determined.